Pengembangan Mikroskop Dengan Mikrokontroler dan Cahaya Monokromatik Untuk Mendeteksi Parasit Malaria - Susanti, Ida; Handayani, Sarwo; Ekowatiningsih, Riyanti; Prasetyorini, Budi; A Yusnita, Endah; Ardianto, Donni Agus; K Widjaya, Sastra (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Malaria still become one of major health burden in Indonesia especially in remote areas of east Indonesia. Golden standard of malaria parasite detection is still microscopic technique using polychromatic light source whether from halogen or natural light source. A microscopic technique has a lot of benefits but still have weaknesses, such as time-consuming and bias on the reading by microscopist, because of artifact in the image. Aims of this study were to designed malaria parasites detection tool that is robust, fast, convenient and clear by minimizing artifact on the slide. Design of this study was laboratory experimental which modified simple microscope into an automatic microscope with table movement and webcam recording using a microcontroller and monochromatic light source. The wavelength of the light sources was 402nm(blue), 532 nm (green) and 650 nm (red), the intensity of each source differed. The reading of the slide image was conducted by two certified microscopists, who read 60 images of a thick and thin slide with three different live stage of Plasmodium falciparum live, which wearing, trophozoite and schizont. This study showed that modification of microscope was succeeded with automatic movement and webcam recording, process time in one step movement and recording approximately 10 seconds or 17minutes for 100 fields of view as confirmation process. The monochromatic light source has proven to give a clear and contrast field of view when the intensities were higher than 40 mW and the certified microscopist able to identified Plasmodium falciparum parasites. Data analysis of microscopist reading used nonparametric statistic Friedman by SPSS showed that correlation between images using monochromatic and polychromatic lights have meaningless differences in a thick and thin slide. However, hemozoin as a marker of Plasmodium falciparum parasite was less detected by monochromatic light used in this study.